2014
DOI: 10.1136/ejhpharm-2014-000483
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the safe and effective use of intravenous gentamicin and vancomycin in Scottish hospitals, and strategies for quality improvement

Abstract: Objectives Avoiding harm when patients interact with healthcare services is a global issue. Guidelines are often produced to improve the prescribing and monitoring of medication with a narrow therapeutic index. Adherence to guidelines may not occur in clinical practice. This paper aims to explore the barriers faced by clinical pharmacists and junior doctors when using complex guidelines to support the prescribing and therapeutic drug monitoring of gentamicin and vancomycin. Methods Twenty-three junior doctors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…Third, we found that junior doctors self-reported a need for additional training in the areas of both clinical review of infected patients, and principles of prescribing. This links to established patient safety agendas, and clearly establishes a need for education on sepsis resuscitation [27], and therapeutic drug monitoring [28, 29] respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Third, we found that junior doctors self-reported a need for additional training in the areas of both clinical review of infected patients, and principles of prescribing. This links to established patient safety agendas, and clearly establishes a need for education on sepsis resuscitation [27], and therapeutic drug monitoring [28, 29] respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that have explored factors influencing uptake of TDM interventions have identified barriers including poor coordination of TDM processes, time constraints, perceived lack of user competency and the prescribing hierarchy [ 8 , 15 , 16 ]. While these findings are useful, systematically identifying barriers and facilitators to uptake using a theory-based framework provides an evidence-based approach to enhance intervention design and achieve successful integration into routine workflow [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…SAPG had previously completed a quality improvement programme for gentamicin and vancomycin 23 and this work on carbapenems used a similar approach. Such programmes utilise several methods to gain intelligence about clinical practice and target areas for improvement.…”
Section: Discussionmentioning
confidence: 99%